Atlantoaxial Subluxation due to an Os Odontoideum in an Achondroplastic Adult: Report of a Case and Review of the Literature - Abolfazl Rahimizadeh; Housain F. Soufiani; Valiolah Hassani; Ava Rahimizadeh (Case Reports in Orthopedics)
The authors report the first example of an adult achondroplastic dwarf with progressive quadriparesis secondary to atlantoaxial subluxation as a consequence of an os odontoideum. Actually, craniocervical region is a frequent site of compression and myelopathy in achondroplasia particularly in children as a result of small foramen magnum and hypertrophied opisthion. Moreover, very rarely in achondroplastic patients, coexistence of atlantoaxial instability as the sequel of os odontoideum can result in further compression of the already compromised cervicomedullary neural tissues, the scenario that has been reported only in five achondroplastic children. Herein, a 39-year-old achondroplastic male suffering such an extremely rare combination is presented. With C1-C2 screw rod instrumentation, atlas arch laminectomy, limited suboccipital craniectomy, and release of dural fibrous bands, reduction, decompression, and stabilization could be achieved properly resulting in steady but progressive recovery.